Critical Discourse in Online News of Nadim Makarim's Statement in Covid-19 Case (Model Teun A. Van Dijk) - M. Nazar; Merlyn Rutumalessy; Nurhasanah Purba (Budapest International Research and Critics University, 2021)
The purpose of this study is to describe the macro and micro structure of the online news discourse text of the Ministry of Education and Culture's Statement in the Middle of the Covid-19 Case. Methods of documentation and content analysis of media texts were used to analyze research data. The results of Analysis is carried out on text elements which are divided into macro and micro structures. Based on the analysis that has been done, it is found that the three discourses fulfill most of the macro and micro elements. The elements that are not found are the rhetorical micro elements of metaphor and expression elements.